HUBUNGAN KADAR ESTROGEN DENGAN KADAR DEOXYPIRIDINOLIN URIN PADA WANITA MENOPAUSE - Wardhiana, I Putu Gede (journal of internal medicine, 2007)
Women in her life will get two land marks, menarche and menopause. Menopause is that point in timewhen permanent cessation of menstruation occurs following the loss of ovarian activity. Women will loss theprotective effect of estrogen, accelerate bone remodeling and get osteoporotic. This study was conducted toevaluate relationship between estrogen level and bone resorption by deoxypyridinoline ekskretion in urine ofmenopausal women. Cross sectional study was done at Obgyn Department, RS Sanglah Denpasar. Population inthis study were women who got cessation their menstruation for 12 months or more, including our inclusioncriteria and the worked in this hospital. We performed deoxypyridinoline urine by high performance liquidchromatography (HPLC) method at Klinik Prodia and basal estradiol level (E2) at Laboratorium Graha TunjungRS Sanglah Denpasar. 52 menopausal women were evaluated, 21.1% with normal estradiol level, and 78.9%low (< 30 pg/ml). We collected 75% normal deoxyyridinoline urine and 25% with high deoxypyridinoline urinelevel (> 7.5 nmol/L), 1 sample with normal estradiol got high deoxypyridinoline urine level. From 41 sample(78.9%) with low estradiol level, twelve (23.1%) with high deoxypyridinoline have the highest osteoporotic riskin their life. Conclusion: 23,1% sample with low estradiol level and high deoxypyridinoline have the highestosteoporotic risk in their life